Beyond Human Resources (IntechOpen, 2023)
Beyond Human Resources - Research Paths Towards a New Understanding of Workforce Management Within Organizations is a concise and pragmatic book about new trends and future lines in human resource management (HRM). It provides an overview of those crucial topics defining today’s HR function. It includes nine chapters offering a framework about urgent HR challenges and lines of actions to understand how HR adapts and innovates to face new organizational realities. This volume is a useful resource for graduate students in the HR discipline.